2010
DOI: 10.1111/j.1440-1681.2010.05462.x
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein 90 mediates cytoprotection by H2S against chemical hypoxia‐induced injury in PC12 cells

Abstract: 1. Increasing evidence indicates that hydrogen sulphide (H₂S) may serve as an important biological cytoprotective agent. Heat shock protein (Hsp) 90 can attenuate stress-induced injury. However, whether Hsp90 mediates the cytoprotective effect of H₂S against chemical hypoxia-induced injury in PC12 cells is not known. 2. In the present study, CoCl₂ (a chemical hypoxia mimetic) was used to treat PC12 cells to create a model of chemical hypoxia. To explore the role of Hsp90 in the cytoprotection afforded by H₂S a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 39 publications
3
27
0
Order By: Relevance
“…GOS combined with VPA induced activation of glycolysis-related proteins (HKII, LDHA) and HYOU1, and resulted in accumulation of the key oxygen-sensitive transcription factor HIF-1α. Stabilization and nuclear translocation of HIF-1α are associated predominantly with hypoxia; in some cases, disruption of TCA cycle, mitochondrial function and increase of cellular stress can also lead to the stabilization of HIF-1α under normoxic conditions, as have been reported in a variety of cells, including DU145, treated with nitric oxide [43], reactive oxygen species and other ER stress reagents [44][45][46], alltrans retinoid acid [47], iron chelator [48], as well as chemical hypoxia mimetic CoCl 2 [49].…”
Section: Discussionmentioning
confidence: 96%
“…GOS combined with VPA induced activation of glycolysis-related proteins (HKII, LDHA) and HYOU1, and resulted in accumulation of the key oxygen-sensitive transcription factor HIF-1α. Stabilization and nuclear translocation of HIF-1α are associated predominantly with hypoxia; in some cases, disruption of TCA cycle, mitochondrial function and increase of cellular stress can also lead to the stabilization of HIF-1α under normoxic conditions, as have been reported in a variety of cells, including DU145, treated with nitric oxide [43], reactive oxygen species and other ER stress reagents [44][45][46], alltrans retinoid acid [47], iron chelator [48], as well as chemical hypoxia mimetic CoCl 2 [49].…”
Section: Discussionmentioning
confidence: 96%
“…H 2 S has also been shown to protect cells from both hypoxiaand hyperoxia-induced redox imbalance and apoptosis (13,83,85,92,101,189,190). The beneficial effects of H 2 S in treating ischemia/reperfusion injury and in pre-and postconditioning have been well documented, and it has been suggested that the beneficial effects of exogenous H 2 S are due to mimicking transient hypoxia, which is also used in conditioning (128).…”
Section: General Metabolismmentioning
confidence: 99%
“…These in vitro findings were mirrored by in vivo observations that H 2 S protects ischemic brain by reinstating GSH levels decreased by oxidative stress. H 2 S has been shown to protect neurons against hypoxic injury by upregulating expression of heat shock protein (HSP) 90 (127,199). HSP90 is a ubiquitous molecule that contributes to cell survival by regulating the folding of various cellular proteins, including survival factors, and by binding to apoptotic protease activating factor-1 (Apaf-1), thereby preventing apoptosis.…”
Section: Cytoprotection and Pharmacological Conditioningmentioning
confidence: 99%